Childbearing and Family Instability: The Impact of Children on Women's Divorce Probability in Iran - Davoud Shahpari Sani; Mohammad Jalal Abbasi Shavazi (مطالعات اجتماعی روان‌شناختی زنان)
In recent years, the incidence of divorce in Iran has risen significantly, making it a pressing social concern. Various demographic and social factors contribute to this trend, with childbearing and the number of children in a family playing a crucial role. This study explores how the presence and number of children influence the likelihood of divorce among Iranian women. A secondary analysis of two-percent sample from the 2016 census data reveals that both childlessness and the number of children in a household significantly affect the probability of divorce among women. The findings indicate that having children reduces the likelihood of divorce, as women who have given birth during their marriage are less likely to divorce than those without children. Moreover, the study demonstrates that a higher number of children is associated with greater marital stability, with families having three or more children exhibiting higher levels of stability compared to others. The results underscore the critical role of childbearing in sustaining marital relationships in Iran. While supporting marriage and family formation, policymakers can enhance family stability by implementing policies and support systems that encourage childbearing.